2014
DOI: 10.1093/nar/gkt1377
|View full text |Cite
|
Sign up to set email alerts
|

The PR-Set7 binding domain of Riz1 is required for the H4K20me1-H3K9me1 trans-tail ‘histone code’ and Riz1 tumor suppressor function

Abstract: PR-Set7/Set8/KMT5a is the sole histone H4 lysine 20 monomethyltransferase (H4K20me1) in metazoans and is essential for proper cell division and genomic stability. We unexpectedly discovered that normal cellular levels of monomethylated histone H3 lysine 9 (H3K9me1) were also dependent on PR-Set7, but independent of its catalytic activity. This observation suggested that PR-Set7 interacts with an H3K9 monomethyltransferase to establish the previously reported H4K20me1-H3K9me1 trans-tail ‘histone code’. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…Notably, the same C-terminal region was found to interact with both the PR domain of PRDM2 and the SET domain of PR-Set7, indicating that these C-terminal truncations may have broader effects besides modulating PRDM2 activity. While the H3K9 methyltransferase activity of PRDM2 has been shown both in vitro and in vivo , it remains unclear whether PRDM2 has monomethyltransferase, dimethyltransferase or dual activity [8, 26, 27]. Moreover, some reports provide evidence for PRDM2 acting as a global enzyme [26], whereas others show its activity to be localized to specific loci [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the same C-terminal region was found to interact with both the PR domain of PRDM2 and the SET domain of PR-Set7, indicating that these C-terminal truncations may have broader effects besides modulating PRDM2 activity. While the H3K9 methyltransferase activity of PRDM2 has been shown both in vitro and in vivo , it remains unclear whether PRDM2 has monomethyltransferase, dimethyltransferase or dual activity [8, 26, 27]. Moreover, some reports provide evidence for PRDM2 acting as a global enzyme [26], whereas others show its activity to be localized to specific loci [27].…”
Section: Discussionmentioning
confidence: 99%
“…While the H3K9 methyltransferase activity of PRDM2 has been shown both in vitro and in vivo , it remains unclear whether PRDM2 has monomethyltransferase, dimethyltransferase or dual activity [8, 26, 27]. Moreover, some reports provide evidence for PRDM2 acting as a global enzyme [26], whereas others show its activity to be localized to specific loci [27]. First, while G9a, a closely related H3K9 methyltransferase, targets the chromatin to place both mono and di methylation of H3K9 ubiquitously, we find that PRDM2 only places H3K9 dimethylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study by Congdon et al showed that RIZ1 was recruited to chromatin by PR-Set7 via direct binding of their C-terminal domains [80]. The RIZ1-PR-Set7 complex was able to establish an H4K30 me1 -H3K9 me1 trans-tail 'histone code' at an ectopic locus to repress gene transcriptions [80].…”
Section: Riz1 Shows Its Tumor Suppressing Activity Through Direct Binmentioning
confidence: 99%
“…The RIZ1-PR-Set7 complex was able to establish an H4K30 me1 -H3K9 me1 trans-tail 'histone code' at an ectopic locus to repress gene transcriptions [80]. Regardless of which route/routes RIZ1 may use to carry out its tumor suppressing functions, it is still unknown how the different functional domains of RIZ proteins coordinate one another during tumor-suppressing by RIZ1 or carcinogenesis by RIZ2.…”
Section: Riz1 Shows Its Tumor Suppressing Activity Through Direct Binmentioning
confidence: 99%